Overcoming PARPi resistance: Preclinical and clinical evidence in ovarian cancer. (March 2021) - Chiappa, M.; Guffanti, F.; Bertoni, F.; Colombo, I.; Damia, G.
Abstract: Ovarian cancer is the fifth cause of cancer-related deaths in women with high grade serous carcinoma (HGSOC) representing the most common histological subtype. Approximately 50 % of HGSOC are characterized by deficiency in homologous recombination (HR), one of the main cellular pathways to repair DNA double strand breaks and one of the well-described mechanisms is the loss of function of the BRCA1 or BRCA2 genes. Inhibition of the poly-ADP-ribose polymerase (PARP) is synthetic lethal with HR deficiency and the use of PARP inhibitors (PARPi) has significantly improved the outcome of patients with HGSOC with a greater benefit in patients with BRCA1/2 deficient tumors. However, intrinsic or acquired resistance to PARPi inevitably occurs in most HGSOC patients. Distinct heterogeneous mechanisms underlying the resistance to PARPi have been described, including a decrease in intracellular drug levels due to upregulation of multidrug efflux pumps, loss of expression/inactivating mutations in the PARP1 protein, restoration of HR and the protection of the replicative fork. Deciphering the molecular mechanisms of resistance to PARPi is of paramount importance towards the development of new treatment strategies and/or novel pharmacological agents to overcome this chemoresistance and optimize the treatment regimen for individual HGSOC patients. The current review summarizes the mechanisms underlying the resistance to PARPi, the available preclinical and clinical data on new combination treatment strategies (with chemotherapy, anti-angiogenic agents and immune checkpoint inhibitors) as well as agents under investigation which target the DNA damage response.